BETWEEN PUBLIC DEBT AND CITIZENSHIP: THE PEDAGOGICAL AND PREVENTIVE ROLE OF CONTROL IN PRESERVING THE SOCIAL FUNCTION OF THE PUBLIC BUDGET - Silva Costa, Alberson; dos Santos Rocha, Anderson; Oliveira Araújo Netto, José; Gorete Borges Figueiredo, Maria; Ferreira Da Silva , Tiago (Revista Gênero e Interdisciplinaridade, 2026)
This article, through a critical effort, seeks to highlight the difficulties of conceiving public policies in an environment of political turbulence and in the face of the forces that control the Brazilian public budget. The Federal public budget has become an arena for class struggle, since, to the detriment of public policies, the Federal budget, from 2016 to 2024, has been drawn up in a way that prioritizes expenses related to rolling over public debt, thus feeding back into the interests of the financial market. The compromise of public accounts due to debt levels makes segments of society vulnerable, while simultaneously fostering tension between classes and increasing poverty. The elaboration of a public budget that considers the complexity of factors connected to the contemporary expression of citizenship requires the participation of different actors, as well as observing the various social demands. In this sense, the budget document proves fundamental in combating inequalities and promoting citizenship.